Traumatic Hearing Loss in the Context of Blast-Related Tympanic Membrane Perforation. Issue 1 (1st January 2017) - Pusz, Max D.; Robitschek, Jon
ABSTRACT: Objective: Identify associated clinical factors and characterize the various forms of hearing loss in the context of blast-related traumatic tympanic membrane (TM) perforation sustained in the combat setting. Methods: A prospective study of 41 patients who sustained a TM perforation secondary to blast injury between 2010 and 2012 while serving in combat. Clinical examinations and audiograms were obtained for all patients by a single-institution Otolaryngology service with comparative data generated from review of pre and post-trauma hearing screens. Follow-up clinical and audiogram data were obtained on all available subjects. Results: 59 TM perforations were documented with audiograms. A conductive hearing loss of 14.8, 22.4, 20.3, and 18.9 dB and sensorineural hearing loss (SNHL) of 18.0, 13.5, 19.9, and 22.0 dB at 500, 1, 000, 3, 000, and 4, 000 Hz, respectively, were observed. 49% of all hearing loss was SNHL. Clinical factors did not correlate statically to hearing loss ( p > 0.05). On average, patients demonstrated a 51% improvement in SNHL at time of follow-up. Conclusion: In the subacute setting, patients with traumatic TM perforations secondary to combat blast injury demonstrate both a conductive hearing loss and SNHL, with 49% of all loss being sensorineural. An average SNHL improvement of 51% was seen at follow-up.